Molecular diversity in coriander (Coriandrum sativum) using RAPD and ISSR markers - CHOUDHARY, SHARDA; SHARMA, RADHESHYAM; JETHRA, G; VISHAL, M K; TRIPATHI, ADITI (The Indian Journal of Agricultural Sciences, 2019)
Coriander (Coriandrum sativum L.) is an annual aromatic herb that belongs to Apiaceae family. Present investigation was carried out to explore the molecular characterization in 24 coriander genotypes. For molecular characterization two DNA based molecular marker techniques, viz. random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR), were used. A total of 27 polymorphic primers (18 random and 9 ISSR) were used. Amplification of genomic DNA of 24 genotypes, using RAPD analysis, yielded 83 fragments, in which 57 (70.46%) were polymorphic. The 9 ISSR primers produced 37 bands across 24 genotypes, of which 17 (49.81%) were polymorphic. Based on the similarity matrix data dendrogram were prepared using UPGMA method. Genotypes were also classified into groups and several subgroups. Principal coordinate analysis (PCA) confirmed the separation of coriander genotypes into groups comparable to those from UPGMA analysis. The high rate of polymorphic lines generated by RAPD and ISSR markers indicated that the method is efficient to analyze molecular diversity in coriander genotypes and that the molecular divergence can be used to establish consistent heterotic groups between coriander genotypes.